ANALISIS KEEFEKTIFAN KALIMAT DALAM JENIS SOAL CERITA PADA PELAJARAN MATEMATIKA SEKOLAH DASAR - Itaristanti Itaristanti (EduMa: Mathematics education learning and teaching, 2014)
This article describes an analytical study on sentences of story-based items of Mathematics. The writer analysis grammatical components, punctuation, and dictions that were use in those test items. The results of analysis found that story-based items errors occured in missformatting word order, writing story details, using prepositions, using inapropriate vocabularies and punctuations, elaborating inefective words, and less coherence. Revising and reconstructing those errors might possibly help students in understanding the core idea of the test items being proposed.